Trade openness and carbon emissions using threshold approach: Evidence from selected Asian countries - Mohd Ashari Bakri; Chia, Yee Ee; Chia, Ricky Chee Jiun (Springer Nature, 2025)
Using the threshold approach, this study provides new insights into the correlation between trade openness and carbon emissions in a sample of Asian countries. The sample includes 22 Asian countries covering the period from 2000 to 2019. The empirical results demonstrate the existence of a threshold effect in terms of trade openness and its relationship with carbon emissions. In particular, the study shows that trade openness has a positive effect on carbon emissions only until a certain threshold is reached; exceeding this threshold leads to a reduction in carbon emissions associated with greater trade openness. The resulting representation of an inverted U-shaped correlation between trade openness and carbon emissions stands up to scrutiny by panel quantile regression and the quadratic methodology (U-test) and confirms its robustness. These findings emphasise the importance of determining an "optimal" level of trade openness, which is essential to effectively govern the mitigation of carbon emissions, as well as to challenge the notion that trade openness inevitably leads to increased carbon emissions. The implications of the Environmental Kuznets Curve (EKC) theory, when accompanied by empirical evidence of knowledge spillovers resulting from trade openness, support innovation pathways that lead to the adoption of greener practices, promoting a cleaner and healthier societal environment.